Iatrogenic Skull Base Defect Accompanied by Brain Injury After Endoscopic Sinus Surgery: A Report of Two Cases - Taegyeong Kim; Junyong Go; Myeong Sang Yu (Journal of Rhinology, 2023)
Although iatrogenic skull base injuries after endoscopic sinus surgery (ESS) are rare (overall complication rate, 0.5%), they can be fatal or cause significant morbidity. Conventionally, skull base injuries were repaired using an external approach. However, in recent years, most skull base injuries after ESS have been repaired using an endoscopic transnasal approach due to its lower morbidity, lower risk of postoperative complications, and shorter hospital stay. We report two cases of iatrogenic skull base injury accompanied by brain injury following ESS and describe the skull base repair techniques employed for each case. In both cases, the skull base defects were successfully repaired using an endoscopic transnasal approach, although craniotomy was also performed in the first case to remove bone fragments from the right frontal base and lateral ventricle. Both patients recovered without residual neurologic deficits.